Epidemiological Trends and Age–Period–Cohort Effects on Dengue Incidence Across High-Risk Regions from 1992 to 2021 - Yu Cao; Hanwu Chen; Hao Wu; Bin Wu; Lu Wang; Xin Liu; Yuyue Yang; Hui Tan; Wei Gao (Tropical Medicine and Infectious Disease)
Dengue, an acute infectious disease caused by the dengue virus, remains a major public health problem in the 21st century. This study investigated the global dengue burden, identified high-risk regions, evaluated the long-term incidence trends, and can inform evidence-based control strategies. Using GBD 2021 data, we analysed the dengue incidence from 1992 to 2021 using age–period–cohort models. We determined the net drift (overall annual percentage change), local drift (annual percentage change for each age group), longitudinal age curves (expected longitudinal age-specific rates), and periods’ (cohorts’) relative risks. In 2021, the global age-standardised incidence rate reached 752.04/100,000 (95% UI: 196.33–1363.35), a 47.26% increase since 1992. High-risk regions included eastern sub-Saharan Africa, Southeast Asia, South Asia, and Latin America and the Caribbean. Southeast Asia experienced the largest rise (65.43%), with a net drift of 2.47% (1992–2021). While individuals aged 5–39 years bore the highest burden, those over 80 faced an elevated risk. Dengue remains a critical public health threat, disproportionately affecting younger populations but increasingly endangering older adults. Targeted interventions in high-risk regions and age groups, coupled with precision public health strategies, are essential to enhance prevention and control efforts.